Studi Kasus tentang Model Komunikasi Organisasi Supervisor dalam Membangun Teamwork di Divisi Broadband & Digital Sales PT TELKOMSEL Branch Ambon, Indonesia - Lucy Pujasari Supratman; M. Haidy Zulfikar Haidy Zulfikar (Fakultas Seni Rupa dan Desain ITB, 2016)
The Division of PT Telkomsel Branch Ambon which do the guerrillas work in the field to promote product knowledge of telkomsel is Broadband and Digital Sales Division. It has a major task in monitoring the sale and purchase of products M-KIOSK Data and Internet package. Supervisor of Broadbad and Digital Sales Division is demanded to have organizational communication skill to make the solidity of teamwork staff in this division. The research method is a descriptive case study. It has run for one month (June-July 2015) with the observation and the interview of Broadband and Digital Sales Supervisor, Mr. Victor Kwando. The results illustrated that by carrying the spirit of The Telkomsel Way, the supervisor can be very successful in transfering teamwork philosophical message to the staff by using open communication between supervisor-staff. The Supervisor of Broadband and Digital Sales establish an open communication within formal and informal organizational structure. This openness led credence to the effectiveness of organizational communication in minimizing misunderstandings among all staff members of Broadband and Digital Sales Division. Keyword: Supervisor of Division, Organizational Communication, Teamwork